2019
DOI: 10.1038/s41598-019-50246-5
|View full text |Cite
|
Sign up to set email alerts
|

Simple lysis of bacterial cells for DNA-based diagnostics using hydrophilic ionic liquids

Abstract: The extraction of nucleic acids from microorganisms for subsequent molecular diagnostic applications is still a tedious and time-consuming procedure. We developed a method for the rapid preparation of genomic DNA from bacteria based on hydrophilic ionic liquids (ILs). First, we tested eight ILs in different buffer systems for their inhibitory effects on quantitative PCR. The cell lysis potential of different IL/buffer combinations was assessed by application on Enterococcus faecalis as a model organism for Gra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 32 publications
(31 reference statements)
0
22
0
Order By: Relevance
“…Then, the tubes were centrifuged at 1000 rpm for 5 minutes and collected the supernatant. The DNA quality was determined by optical density at 260/280 nm, and 5 microliters of aliquot were used for PCR [15].…”
Section: Bacteria Dna Extractionmentioning
confidence: 99%
“…Then, the tubes were centrifuged at 1000 rpm for 5 minutes and collected the supernatant. The DNA quality was determined by optical density at 260/280 nm, and 5 microliters of aliquot were used for PCR [15].…”
Section: Bacteria Dna Extractionmentioning
confidence: 99%
“…Physical lysis can include freeze-thaw ( Shao et al, 2012 ), heat, cavitation ( Liu et al, 2020 ), and ultrasonic ( Han et al, 2019 ) methods. Chemical lysis uses ionic alkali solutions or detergents to disrupt the bacterial cell membrane ( Chapela et al, 2007 ; Martzy et al, 2019 ). Enzymatic lysis is accomplished through the application of enzymes such as proteinase k and lysozyme ( Gill et al, 2016 ).…”
Section: Wet Lab Considerationsmentioning
confidence: 99%
“…There are few studies which reported isolation of DNA from gram positive bacteria even without using lysozyme [35,36] Yuan et al [37] reported that lysozyme alone is not efficient in extracting DNA from human microbiome (especially gram positive bacteria). Shahriar et al [38] 5).…”
Section: Gram +Ve Gram -Ve Gram Variable Othersmentioning
confidence: 99%